Real things on social integration of handicapped people - Inacia Sátiro Xavier de França; Lorita Marlena Freitag Pagliuca (Rev Rene)
This is na article based on a speech analysis, in accordance with Orlandi (2001), order to analyze discursive formations concerning social integration of Handicapped People – HP, from 1981 through 2001. The analytical device was constituted by the corpus of the analysis, composed of texts on the integration of the HP, of guiding questions on the analyses and of the thought of authors from several fields that supported the analysis. The analytical process exposed discursive formations of the State, of the Rehabilitation Team, of society, family and HP concerning social integration, clearing questions opeople.